Tertiary English Language Teachers’ Perceptions toward Self-reflection and Teacher Collaboration on Learning and Professional Development - Choopun, Jittima; Tuppoom, Jirayu (Journal of Liberal Arts Prince of Songkla University, 2019)
This paper reports on preliminary study results of Thai tertiary English language teachers’ perceptions toward self-reflection and teacher collaboration on learning and professional development. The data was collected from a questionnaire and semi-structured interview which were responded by 32 Thai tertiary English language teachers who worked in a government university in the southern region of Thailand in the academic year 2015. The purposive sampling method was used to select the participants. The questionnaire data was analyzed by means of frequencies and percentages. The interview data was analyzed thematically. The findings demonstrated that the participants had positive perceptions and appreciated the value of self-reflection and teacher collaboration on their learning and professional development. They self-reflected on their teachings on a regular basis both reflection-in-action and reflection-on-action. The interview results revealed 4 main themes of perceptions toward self-reflection: internal desire to solve problems, changing teaching practice, enhancing English language competence, and essential part of logical and critical thinking. The study also explored 3 main themes of perceptions toward teacher collaboration: effective interpersonal skills, scaffold to individual development, and strengthen effective teaching.